2018 CARICOM Regional Energy Efficiency Building Code (CARICOM Regional Organisation for Standards and Quality St. MichaelBB, 2019)
CREEBC was established to meet the needs of the Caribbean and other countries in a tropical environment. It estabishes minimum energy efficiency requirements for buildings using prescriptive and performance-related provisions inclusive of building envelope, cooling system, ventilation, pumping, lighting and the service water-heating systems in buildings. The technical requirements of this code are the product of regional and international expertise.
Keywords: ENERGY